Nodular canine transmissible venereal tumour in extragenital area: Case report - Gabriela Ramos Leal; Danielle Porcari Alves; Gabriela Soares Gravina; Tatiana Rezende Vieira (Pubvet, 2022)
Canine transmissible venereal tumour (TVT) is a contagious venereal round-cell tumour with high incidence in stray dogs. TVT is commonly transmitted by copula, so it occurs mainly at the mucous membrane of the external genital of male and female dogs. This study aimed to report a case of a dog with TVT at an extragenital area, presented as a nodular cutaneous lesion. The dog presented a large nodular mass located in the cervical region. Clinical examination also revealed micronodules in the left forearm and an ulcerated nodule located on the back. After the diagnosis of TVT by cytological examination, a chemotherapeutic protocol based on vincristine sulphate (0.75 mg / m2) was established in four applications, with 7 days of interval. The treatment was effective in the regression of nodular lesions, observed clinically at the end of the protocol. Although it has already been described metastasis, TVT complications usually are related to the growth of the tumor in the tissue in which it is implanted. Our study confirmed that the treatment of intravenous administration of vincristine sulphate weekly for 4 weeks was effective in the remission of the nodules. This report indicates that TVT extragenital must be present among the differential diagnoses in the occurrence of cutaneous nodules in the canine patient when considering its historic.